Reductions in disease activity in the AMPLE trial: clinical response by baseline disease duration. Issue 1 (19th April 2016) - Schiff, Michael; Weinblatt, Michael E; Valente, Robert; Citera, Gustavo; Maldonado, Michael; Massarotti, Elena; Yazici, Yusuf; Fleischmann, Roy
Abstract : Objectives: To evaluate clinical response by baseline disease duration using 2-year data from the AMPLE trial. Methods: Patients were randomised to subcutaneous abatacept 125 mg weekly or adalimumab 40 mg bi-weekly, with background methotrexate. As part of a post hoc analysis, the achievement of validated definitions of remission (Clinical Disease Activity Index (CDAI) ≤2.8, Simplified Disease Activity Index (SDAI) ≤3.3, Routine Assessment of Patient Index Data 3 (RAPID3) ≤3.0, Boolean score ≤1), low disease activity (CDAI <10, SDAI <11, RAPID3 ≤6.0), Health Assessment Questionnaire-Disability Index response and American College of Rheumatology responses were evaluated by baseline disease duration (≤6 vs >6 months). Disease Activity Score 28 (C-reactive protein) <2.6 or ≤3.2 and radiographic non-progression in patients achieving remission were also evaluated. Results: A total of 646 patients were randomised and treated (abatacept, n=318; adalimumab, n=328). In both treatment groups, comparable responses were achieved in patients with early rheumatoid arthritis (≤6 months) and in those with later disease (>6 months) across multiple clinical measures. Conclusions: Abatacept or adalimumab with background methotrexate were associated with similar onset and sustainability of response over 2 years. Patients treated early or later in the disease course achieved comparable clinical responses. Trial registration number: NCT00929864, Post-results.